2009
DOI: 10.1097/dad.0b013e3181914e6f
|View full text |Cite
|
Sign up to set email alerts
|

Dermatomyofibroma: Clinicopathologic and Immunohistochemical Analysis of 56 Cases and Reappraisal of a Rare and Distinct Cutaneous Neoplasm

Abstract: Dermatomyofibroma represents a rare and distinct benign cutaneous mesenchymal neoplasm of fibroblastic/myofibroblastic differentiation. A series of 56 cases of dermatomyofibroma has been analyzed to further characterize the clinicopathologic spectrum of this entity. Forty patients were female and 8 were male (gender was unknown in 8 cases). Patients' age ranged from 3 to 51 years (mean 30.8 years, median 30 years). Interestingly, 6 patients were younger than 16 years, and in this age group, 3 male and 3 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 16 publications
7
91
1
5
Order By: Relevance
“…Dermatomyofibroma develops most frequently in young female patients, and commonly occurs on the shoulder, upper arm, axilla, neck, and/or the upper trunk. In a recent study, female and male children and adolescent atients were reported to be affected equally, in contrast to the female dominant pattern in adults2.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Dermatomyofibroma develops most frequently in young female patients, and commonly occurs on the shoulder, upper arm, axilla, neck, and/or the upper trunk. In a recent study, female and male children and adolescent atients were reported to be affected equally, in contrast to the female dominant pattern in adults2.…”
Section: Discussionmentioning
confidence: 92%
“…Among those, three cases occurred in the infantile period1-6. It has been suggested that dermatomyofibroma in male children tends to show spontaneous regression after childhood, whereas the lesions continue to grow in female patients, possibly due to the effects of female hormones2,5. However, there is no proof for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations